In-flight medical emergencies during airline operations: a survey of physicians on the incidence, nature, and available medical equipment - Hinkelbein J; Neuhaus C; Böhm L; Kalina S; Braunecker S (Open Access Emergency Medicine, 2017)
Jochen Hinkelbein,1,2 Christopher Neuhaus,2,3 Lennert Böhm,1 Steffen Kalina,1 Stefan Braunecker1,2 1Department of Anaesthesiology and Intensive Care Medicine, University Hospital of Cologne, Cologne, 2Working group “Emergency Medicine and Air Rescue”, German Society for Aviation and Space Medicine (DGLRM), Munich, 3Department of Anesthesiology, Heidelberg University Hospital, Heidelberg, Germany Background: Data on the incidence of in-flight medical emergencies on-board civil aircraft are uncommon and rarely published. Such data could provide information regarding required medical equipment on-board aircraft and requisite training for cabin crew. The aim of the present study was to gather data on the incidences, nature, and medical equipment for in-flight medical emergencies by way of a survey of physician members of a German aerospace medical society.Materials and methods: Using unipark.de (QuestBack GmbH, Cologne, Germany), an online survey was developed and used to gather specific information. Members of the German Society for Aviation and Space Medicine (Deutsche Gesellschaft für Luft- und Raumfahrtmedizin e.V.; DGLRM) were invited to participate in the survey during a 4-week period (21 March 2015 to 20 April 2015). Chi-square test was used for statistical analysis (p<0.05 was considered significant).Results: Altogether, 121 members of the society responded to the survey (n=335 sent out). Of the 121 respondents, n=54 (44.6%) of the participants (89.9% male and 10.1% female; mean age, 54.1 years; n=121) were involved in at least one in-flight medical emergency. Demographic parameters in this survey were in concordance with the society members’ demographics. The mean duration of flights was 5.7 hours and the respondents performed 7.1 airline flights per year (median). Cardiovascular (40.0%) and neurological disorders (17.8%) were the most frequent diagnoses. The medical equipment (78.7%) provided was sufficient. An emergency diversion was undertaken in 10.6% of the cases. Although using a different method of data acquisition, this survey confirms previous data on the nature of emergencies and gives plausible numbers.Conclusion: Our data strongly argue for the establishment of a standardized database for recording the incidence and nature of in-flight medical emergencies. Such a database could inform on required medical equipment and cabin crew training. Keywords: in-flight medical emergencies, medical assistance, emergency medical equipment, on-board emergencies, first aid